Effect of substitution ratio of wheat flour with coconut dregs and avocado seed flour as gluten-free flour on the chemical characteristics of white bread - Delsi Anjarwati; Winda Dwi Oktarini; Ari Setiawan; Nabilla Dhiya Ulhaq; DESIANA NURIZA PUTRI (AGROINTEK, 2023)
Analysis of the chemical properties of white bread whose formulation is modified by substitution of coconut dregs flour and avocado seed is very important to do to find out how much increase in dietary fiber content in white bread and to determine the content contained in it, which can affect the quality of the white bread. The research aimed to study the effects of coconut dregs flour and avocado seed ratios on chemical properties and daily index sufficiency of white bread. This research used a randomized block design with one factor, the ratio of white flour, coconut dregs flour and avocado seed flour is P0 (control), P1 (90%:5%:5%), P2 (85%:10%:5%), P3 (80%:15%:5%), P4 (75%:20%:5%), and P5 (70%:25%:5%). The results of the research showed that P5 white bread had the lowest water content of 35.10%, P0 white bread had the lowest ash content of 0.66%, P5 white bread had the highest fat content of 12.34%, P0 white bread had the highest protein content of 9.11%, P1 white bread has the highest carbohydrate content of 45.43%, P5 white bread has the highest crude fiber and dietary fiber content, respectively 7.78% and 17.92%. The substitution ratio of coconut dregs flour and avocado seed flour in all treatments does not significantly affect the value of the daily index sufficiency.